Mozambique: Off-track or temporarily sidelined? - Channing Arndt; E. Samuel Jones; Finn Tarp (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2015)
Since 1994, a great deal has been accomplished. We argue that poverty reduction was temporarily sidelined in the 2000s. A series of shocks, especially the fuel and food price crisis of 2008, combined with poor productivity growth in agriculture and a weather shock, undermined progress in measured consumption poverty. We expect progress in poverty reduction to resume. These shocks also exposed persistent weaknesses in development strategies and programmes. Nevertheless, Mozambique has the potential to achieve rapid and broad-based economic and social progress. With key reforms and success in maintaining peace and stability, it will.
Keywords: D63; I32; O47; O55; 330; Mozambique; consumption poverty; growth; inequality; non-monetary measures of well-being